2012
DOI: 10.5402/2012/198590
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Mn-Doped Ge Nanostructures

Abstract: With the seemly limit of scaling on CMOS microelectronics fast approaching, spintronics has received enormous attention as it promises next-generation nanometric magnetoelectronic devices; particularly, the electric field control of ferromagnetic transition in dilute magnetic semiconductor (DMS) systems offers the magnetoelectronic devices a potential for low power consumption and low variability. Special attention has been given to technologically important group IV semiconductor based DMSs, with a prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 155 publications
(295 reference statements)
1
12
0
Order By: Relevance
“…The picture in figure 1(d) was further analyzed using clustering-based image thresholding, exploiting Otsu's method. This analysis, presented in figure 1(e), was carried out on a surface of 12×10 -8 cm 2 and confirmed that distribution of dots equivalent radii is broad indeed (2 nm < r < 22 nm). However, two peaks could be identified: one centered at r ∼ 4 nm and a second at r ∼ 15 nm.…”
Section: Aip Advances 8 056414 (2018)supporting
confidence: 70%
See 2 more Smart Citations
“…The picture in figure 1(d) was further analyzed using clustering-based image thresholding, exploiting Otsu's method. This analysis, presented in figure 1(e), was carried out on a surface of 12×10 -8 cm 2 and confirmed that distribution of dots equivalent radii is broad indeed (2 nm < r < 22 nm). However, two peaks could be identified: one centered at r ∼ 4 nm and a second at r ∼ 15 nm.…”
Section: Aip Advances 8 056414 (2018)supporting
confidence: 70%
“…The discovery of room-temperature ferromagnetism in germanium manganese (Ge 1-x Mn x ) quantum dots obtained via heteroepitaxy on silicon 2 had attracted much attention due to the possibility to realize electric field control of ferromagnetism, 3 and indicates Ge 1-x Mn x alloys as good candidates for applications in spintronics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By plotting the value of dM/dT as a function of T ( Figure 5(b)) it is possible to identify two characteristic temperatures for the samples aGeMn2.2 (10%) and aGeMn2.3 (17%) that are at ∼ 12.5 K and ∼ 14.7 K respectively. By defining these two values as the Curie temperatures, we can fit the FC curves for T < T C by employing Equation (8). The two fits in Figure 5(d) display the good agreement between the experimental dependence and Equation (8), whereas this correspondence starts to vanish above T C .…”
Section: Static Magnetic Measurementsmentioning
confidence: 67%
“…in the case of Ge 1-x Mn x DMS, T C ∼ 270K (Ge 3 Mn 5 ) and T C ∼ 296K (Ge 8 Mn 11 ). [7,8] In recent decades diluted magnetic alloys, such as Fe or Mn dispersed in Cu, have been extensively studied. [9,10] In these metallic alloys, the low-density spins could be treated as a perturbation of the Fermi liquid, representing the host non-magnetic metal.…”
mentioning
confidence: 99%